2008
DOI: 10.1051/0004-6361:200810303
|View full text |Cite
|
Sign up to set email alerts
|

First detection of CO lines in a water fountain star

Abstract: Context. Water fountain stars are very young post-AGB stars with high velocity water maser jets. They are the best objects in which to study the onset of bipolar jets from evolved stars due to their young dynamical ages. However, none of them has been observed in any thermal lines. Aims. We aim to search for CO lines in the water fountain star IRAS 16342-3814 and investigate the properties of its thermal gas. Methods. The proximity, peculiar stellar velocity and high Galactic latitude of IRAS 16342-3814 make a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
23
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 28 publications
8
23
0
Order By: Relevance
“…The applicability of the expansion velocity -main sequence mass relation, which yields this low mass, to individual sources is however highly uncertain. For example observations of CO and its isotopologues may provide further mass estimates (e.g., He et al 2008). Furthermore, Very Long Baseline Interferometry (VLBI) observations will be needed to derive a more accurate distance, and constrain internal kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of the expansion velocity -main sequence mass relation, which yields this low mass, to individual sources is however highly uncertain. For example observations of CO and its isotopologues may provide further mass estimates (e.g., He et al 2008). Furthermore, Very Long Baseline Interferometry (VLBI) observations will be needed to derive a more accurate distance, and constrain internal kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…CO and 13 CO spectra have been widely observed in AGB and post-AGB stars; modelling them has been used to determine the mass-loss rate, the total mass, and other physical parameters (see, for example, Teyssier et al 2006). So far, IRAS 16342-3814 is the only WF where thermal line emission has been unambiguously reported (He et al 2008;Imai et al 2009). From the detection of the CO and (tentatively) 13 CO J = 2 → 1 lines, He et al (2008) have determined an expansion velocity of 46 km s −1 , higher than that expected in an AGB envelope (typically 15 km s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, IRAS 16342-3814 is the only WF where thermal line emission has been unambiguously reported (He et al 2008;Imai et al 2009). From the detection of the CO and (tentatively) 13 CO J = 2 → 1 lines, He et al (2008) have determined an expansion velocity of 46 km s −1 , higher than that expected in an AGB envelope (typically 15 km s −1 ). Surprisingly, the CO J = 3 → 2 line reported recently (Imai et al 2012) shows a different kinematics, depicting an even broader profile (>200 km s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…He et al (2008) detected a low 12 CO/ 13 CO intensity ratio of 1.7 and concluded that 12 C is being converted into 13 C via the hot bottom burning process, suggesting that the initial mass of the central star is as high as > ∼ 5 M . Another characteristic of this object is high-velocity maser components.…”
Section: Introductionmentioning
confidence: 99%